Recent Developments in Cyber Security Research within Information Systems: A Systematic Literature Review (2021–2025) - Haya Fadiyah Hanin; Sambas Ade Kesuma; Keulana Erwin; Fahmi Natigor Nasution (Pusat Riset dan Inovasi Nasional, 2026)
Cybersecurity has become a critical concern for organizations as digital transformation accelerates across all sectors, exposing information systems to increasingly sophisticated threats. This studi aims to analyze and systhesize the dispersed academis literature on cybersecurity in the context of information systems, eith particular focus on the business and accounting domain. A systematic review (SLR) approach was adopted following the PRISMA framework. A total of 28 open-access articles published between 2024 and 2025 were selected from the Scopus database, applying strict inclusion creiteria covering subject area, document type, languange, and source type. Analysis reveals five dominant research themes: AI and security technology, policy, governance, and framework, security behavior and culture, cybersecurity in business context, and digital risk management. Publications are concentrated in 23 journals across 23 countries, with the United States as the leading contributor. Quantitative methods dominate the research landscape while the individual level emerges as the most frequently explored unit of analysis. The findings indicate that effective cybersecurity in informations systems is inherently socio-technical, requiring the simultaneous advancement of AI-based defenses, sound governance frameworks, and human-centered security behavior. This study provides an up-to-date overview of the cybersecurity research landscape in information systems for 2024-2025, identifies emerging trend, and proposes a future reseacrh agenda, particularly for developing country contexts that remain underrepresented in the literature.